PENGEMBANGAN E-HANDOUT MESIN BUBUT KELAS XI DI SMK NEGERI 2 BITUNG - ronaldo kresmito pitoy; Herdy Liow; Jenly Manongo; Robert Munaisache (Pendidikan Teknik Mesin, 2021)
DEVELOPMENT OF CLASS XI LATHE E-HANDOUT IN SMK NEGERI 2 BITUNG By: RONALDO KRESMITO PITOY 14212084 Supervisor : Dr. H. Dj. Liow, ST, M.Eng Ir. D. J. I. Manongko, M.Eng ABSTRACT This research is motivated by the limited or incomplete handouts in school in terms of material explanation and the number of handouts, the lack of handouts available in schools causes students to be unable to learn independently. The purpose of this research is to produce lathe handout products for class XI. This research is a development research (Research and Development) using the ADDIE (Branch 2009) research model, namely (A) analysis, (D) esign, (D) development, (I) implementation, and (E) valuation. The sample taken was 5 people for the small group test. The data analysis technique was carried out descriptively. Students are given a questionnaire to see student responses to the lathe e-handout, the student responses are more in the 4.5 range and are in very good qualifications. Based on the results of the study, it can be concluded that the e-handout product for class XI has been produced with the appropriate qualifications for use. Keywords: E-Handout, Research and Development, Lathe.